KOORDINASI TIM PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK - Dewi Kartini (Universitas Riau, 2015)
Coordination The Central Team Integrated Services Center for Women and Children. This study aimed to obtain in-depth description of how coordination of employee Tim Integrated Services Center for Women’s Empowerment and Child (P2TP2A) Riau Province. The informants are the core team (P2TP2A), community leaders and families of the victims. Data collected by interview, observation and documentation study. Analysis of data using an interactive model. The results showed that the factors that affect the coordination consisting of unity of action, communication, division of labor and discipline has been going according to the expectations of all parties, where the factor of unity of action is the factor most powerful influence on the achievements of the implementation of the settlement of cases P2TP2A handled by Riau Province during this time. Meanwhile, related to the coordination of existing P2TP2A Riau Province today has gone well.